Perspectives for Forkhead box transcription factors in diabetic cardiomyopathy: Their therapeutic potential and possible effects of salvianolic acids - Han, Ronghui; Huang, Hemeng; Xia, Weiyi; Liu, Jingjin; Luo, Hui; Tang, Jing; Xia, Zhengyuan (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DCM) is the main cause of morbidity and mortality in diabetic cardiovascular complications, which is initially characterized by cardiac hypertrophy, myocardial fibrosis, dysfunctional remodeling, and diastolic dysfunction, followed by systolic dysfunction, and eventually by clinical heart failure. Molecular mechanisms underlying these pathological changes in the diabetic heart are complicated and multifactorial, including but not limited to insulin resistance, oxidative stress, lipotoxicity, cardiomyocytes apoptosis or autophagy, inflammatory response and myocardial metabolic dysfunction. With the development of molecular biology technology, accumulating evidence demonstrates that members of the class O of Forkhead box (FoxO) transcription factors is vital for maintaining cardiomyocyte metabolism and cell survival via modulating a wide variety of cellular functions as concerning phosphorylation, acetylation, ubiquitination, arginine methylation, and O-glycosylation. In this review, we highlight and summarize the latest advances of two types of FoxO (predominately FoxO1 and FoxO3a) that are abundantly expressed in cardiac tissue and whose levels of gene and protein expressions are changed during the progression of DCM, aiming to provide valuable perspectives into the pathogenesis of diabetic cardiovascular complications and discuss their therapeutic potential and possible effects of natural product salvianolic acids.